Using Adobe Flash-Based Game to Educate Children about Covid-19 - Ratih Laily Nurjanah; Sri Waluyo; Ahmad Fauzi Anggi Ariesta Kusuma (Metathesis: Journal of English Language, Literature, and Teaching, 2020)
Some protocols published by WHO during this outbreak are to keep safe distance with minimum 1 meter, wear face masks especially in public places. Other health protocols such as wash hands using soap or hand sanitizer or have shower after being at home from work or other places are also being campaigned by government. However, most information provided used difficult language and hard to understand by children. This study therefore attempts to combine all of those backgrounds by creating a digital game related to Covid-19 which hopefully will provide positive contribution during this hard time. Furthermore, this game attempts to cover the right for children to access online gaming while keep educating them and protecting them from negative influences. This research employed Doppler Interactive Game Design Life Cycle as proposed by Joshua McGracth which basically consists of 6 iterative phases (Ramadan & Widyani, 2013), but here stopped at the testing process. Software used to develop this game were Adobe Flash and Adobe Premiere. The development if this game is also assessed appropriate by parents and English teachers in terms of the layout, the language or terms appropriateness, and the effectiveness.